2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--19874
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Listen: An Ethnographic Approach to Engineering Ethics Education

Abstract: Studies (STS) at Virginia Tech. For the past 6 years, she has conducted research on the historic 2001-2004 Washington, DC lead-in-drinking-water contamination. This work exposed wrongdoing and unethical behavior on the part of local and federal government agencies. In 2010, Dr. Lambrinidou co-conceived and co-taught the new graduate level engineering ethics class "Engineering Ethics and the Public." Her previous research focused on hospice and pediatric cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This, however, should not be the case because every day, engineers make highly complicated and critical decisions that directly affect the health and welfare of the public. Even though the work of the engineers is technical, there are broader social components associated with their work that cannot be ignored (Lambrinidou and Edwards, 2013). In fact, previous literature has shown that engineers who do not take into account the public concerns about their projects are much more vulnerable to self-interest, self-delusion, and institutional pressures that contribute to unethical Nguyen, Luan Engineering a Culture of Public Engagement in the Trump Era-Challenging the Status Quo and substandard decisions, leaving negative impacts on society (Lambrinidou and Edwards, 2013).…”
Section: Nguyen Luanmentioning
confidence: 99%
“…This, however, should not be the case because every day, engineers make highly complicated and critical decisions that directly affect the health and welfare of the public. Even though the work of the engineers is technical, there are broader social components associated with their work that cannot be ignored (Lambrinidou and Edwards, 2013). In fact, previous literature has shown that engineers who do not take into account the public concerns about their projects are much more vulnerable to self-interest, self-delusion, and institutional pressures that contribute to unethical Nguyen, Luan Engineering a Culture of Public Engagement in the Trump Era-Challenging the Status Quo and substandard decisions, leaving negative impacts on society (Lambrinidou and Edwards, 2013).…”
Section: Nguyen Luanmentioning
confidence: 99%
“…Many of our team members drew motivation from a Virginia Tech graduate class "Engineering Ethics and the Public". 4 Still, be cognizant that you are asking a great deal from your team. To date, our team has volunteered about six person-years effort on the Flint disaster.…”
mentioning
confidence: 99%
“…The course is a three-credit elective course offered annually to engineering students. The overall course itself was originally co-conceived and co-developed by an engineer, one of the authors of this paper, and a medical ethnographer, with the support of the National Science Foundation (NSF) [1]. The learning objectives, topics, and assignments are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…A major motivation in developing this course was to prioritize listening as a core component of engineering practice and to consider the perspectives of non-experts (i.e., non-engineers, nonscientists, non-architects, etc.) in conventional decision-making processes [1], [2]. The course provides practices in and reflection on empathetic and in-depth listening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation